2015
DOI: 10.2967/jnumed.114.152504
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activity of Red Nucleus and Its Correlation with Cerebral Cortex and Cerebellum: A Study Using a High-Resolution Semiconductor PET System

Abstract: The red nucleus (RN) is a pair of small gray matter structures located in the midbrain and involved in muscle movement and cognitive functions. This retrospective study aimed to investigate the metabolism of human RN and its correlation to other brain regions. Methods:We developed a high-resolution semiconductor PET system to image small brain structures. Twenty patients without neurologic disorders underwent whole-brain scanning after injection of 400 MBq of 18 F-FDG. The individual brain 18 F-FDG PET images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Functional neuroimaging studies suggest that the RN is functionally connected to brain areas related to WM, including prefrontal cortical areas (BA 45; BA 46; BA 47), the insula, the hippocampus (BA 11 and precuneus) and the occipital cortex [51]. In addition, a recent study [52] using high resolution PET showed very similar results to the study [51] and suggested that the right RN showed strong ipsilateral metabolic correlations with association cortices, while the left RN showed a more bilateral pattern of connectivity with the cerebral cortex [52]. These findings suggest that the RN shows strong connectivity with cortical areas that are either part of the “core” WM network [15] or had shown activity during visuospatial WM tasks, and several of them showed activity and connectivity effects in our healthy sample.…”
Section: Discussionmentioning
confidence: 99%
“…Functional neuroimaging studies suggest that the RN is functionally connected to brain areas related to WM, including prefrontal cortical areas (BA 45; BA 46; BA 47), the insula, the hippocampus (BA 11 and precuneus) and the occipital cortex [51]. In addition, a recent study [52] using high resolution PET showed very similar results to the study [51] and suggested that the right RN showed strong ipsilateral metabolic correlations with association cortices, while the left RN showed a more bilateral pattern of connectivity with the cerebral cortex [52]. These findings suggest that the RN shows strong connectivity with cortical areas that are either part of the “core” WM network [15] or had shown activity during visuospatial WM tasks, and several of them showed activity and connectivity effects in our healthy sample.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the RN in humans receives afferents from the dentate nucleus of cerebellum and the cerebral cortex (Habas and Cabanis, 2007); however, new techniques like diffusion tensor imaging (DTI) provide anatomical information about several regions of the cerebral cortex that connect to the RN, including the prefrontal, sensorimotor, premotor lateral and medial prefrontal, and cingulate cortices. Also, the RN has anatomical connections to the thalamus, paracentral lobule, precentral gyrus, and superior frontal gyrus, and is less connected to the caudal middle frontal gyrus, inferior and superior parietal lobules, and middle temporal gyrus (Hirata et al, 2015;Milardi et al, 2016).…”
Section: Red Nucleus In Humansmentioning
confidence: 99%
“…The human RN plays a critical role in motor control and is involved in the regulation of muscle tension, motor responses, motor learning, and sensory discrimination (Liu et al, 2000). Recently, it has been associated with cognitive functions related to salience detection, executive control (Hirata et al, 2015;Cacciola et al, 2019), and emotion processing (Zhang et al, 2015).…”
Section: Red Nucleus In Humansmentioning
confidence: 99%
“…The Substantia Nigra (pars compacta) along with the nigrostriatal dopaminergic pathways are also likely compromised in PD [34]. Cognitive symptoms, such as intellectual fatigability, decreased verbal fluency, and discrete memory impairment, have been reported in relation to Red Nucleus deficits [35,36]. Finally, increased activity in the Subthalamic Nucleus activity was reported during decisions requiring high cognitive burden and when linking cognitive and motor processes [37].…”
Section: Pivotal Regions For Cognitive and Motor Decline Predictionmentioning
confidence: 99%